2022
DOI: 10.1109/access.2022.3160187
|View full text |Cite
|
Sign up to set email alerts
|

The Tensor Multi-Linear Channel and Its Shannon Capacity

Abstract: Tensors are multi-way arrays which can be used to model systems spanning many domains. This work proposes to use tensors for characterizing, analyzing, and designing multi-domain communication systems. Most modern day communication systems make use of coding and modulation across different domains such as space, frequency, time. Hence a unified mathematical framework characterizing such a multiple-domain system in an intuitive manner is well needed. In this paper, we present such a unified framework that chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 108 publications
(299 reference statements)
0
23
0
Order By: Relevance
“…This paper uses several tensor algebra results such as the Einstein product, outer product, tensor inverse, Hermitian. A detailed review of all such relevant tensor algebra results can be found in [27], [43].…”
Section: The Tensor I-mmse Relationmentioning
confidence: 99%
See 4 more Smart Citations
“…This paper uses several tensor algebra results such as the Einstein product, outer product, tensor inverse, Hermitian. A detailed review of all such relevant tensor algebra results can be found in [27], [43].…”
Section: The Tensor I-mmse Relationmentioning
confidence: 99%
“…The received signal is modelled as a fourth order tensor for MIMO OFDM in [24]. Similar application of tensors for signal representation in several multi-domain systems such as Filter bank-based Multi-carrier (FBMC) [25], cellular networks [26], MIMO multiple access and interference channels [27], Nonorthogonal Multiple Access (NOMA) systems [28], have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations